Magnesium isotopic composition of modern human teeth enamel and its implications for dietary reconstructions - Gao, Fan; Zhang, Pan; Liu, Keyu; Ling, Xue; Huang, Kang-Jun (Frontiers in Earth Science, 2023)
Metal stable isotopic composition of dental enamel is a novel proxy for reconstructing human dietary structure. Magnesium is the second most prevalent element in teeth only after calcium. Significant isotopic fractionation of Mg isotopes during biological processes implies its great advantages in reconstructing human recipes. To evaluate the potential of the Mg isotopic composition of dental enamel in learning the human dietary structure, elemental and Mg isotopic analyses were performed on the modern human teeth from regions in northern and southern China with various dietary characteristics. Our findings reveal that southern Chinese teeth enamel has higher Mg contents and heavier Mg isotopic compositions (-0.69‰ for SN and -0.66‰ for HZ) than those of their northern counterparts (-1.27‰ for WN and -1.33‰ for PY). Such discrepancy cannot be attributed to the provenance heterogeneity or individual metabolic processes. Instead, the correlations between cereal-based dietary patterns and the δ26Mg in dental 27 enamel demonstrate that the structure of the staple diet is more responsible for the Mg isotopic signatures. Moreover, heavier Mg isotopic compositions have been observed in dental enamel of individuals with higher rice and lower wheat in the diet, indicating that Mg isotopes are a promising tracer for rebuilding individual or population plant-based dietary structures as well as distinguishing more specific species within C3 plants. These findings suggest that Mg isotopes in teeth enamel have the great potential to 33 better identify the food composition and constrain the diet structure of ancient humans.